Stigma and discrimination among health care providers towards people living with HIV/AIDS (PLWHA) - Mohamed Osman Elamin; Yahiya Rajaa; Hamed Ademola Adetunji; Sufian Khalid; Remah Siddiq (International Journal of Public Health Science (IJPHS), 2019)
Stigma and discrimination among medical care providers (MCPs) towards HIV patients is a common observed problem that can compromise effectiveness of prevention and treatment efforts by discouraging individuals from being tested or seeking information on how to protect themselves and others. This research aimed to determine the existence of stigma and discrimination among health care providers towards people living with HIV and AIDS (PLWHA) in River Nile state. A descriptive cross sectional hospital based study conducted in Atbara, Edamer and Berber hospitals. Questionnaire containing six parts covering the personal data, knowledge about HIV, attitude, availability of PPDs and discriminatory practices of MCPs was used. The data was analyzed using the SPSS. Three hundred and nighty participated consisting of 136 doctors, 219 nurses, and 35 midwives. Out of these, 68.2% of participants had overall satisfactory knowledge, 30% had good knowledge, while only 1.8% had poor knowledge. Majority (74.4%) stated that MCPs were discriminatory in their practices towards HIV patients. There wa correlation between common discriminatory practices and total attitude, and availability of PPDs (p<0.05). No correlation between the common discriminatory practices and total knowledge scores.